Discovery of novel KRAS‒PDEδ inhibitors with potent activity in patient-derived human pancreatic tumor xenograft models - Long Chen; Jing Zhang; Xinjing Wang; Yu Li; Lu Zhou; Xiongxiong Lu; Guoqiang Dong; Chunquan Sheng (Elsevier, 2022)
KRAS‒PDEδ interaction is revealed as a promising target for suppressing the function of mutant KRAS. The bottleneck in clinical development of PDEδ inhibitors is the poor antitumor activity of known chemotypes. Here, we identified novel spiro-cyclic PDEδ inhibitors with potent antitumor activity both in vitro and in vivo. In particular, compound 36l (KD = 127 ± 16 nmol/L) effectively bound to PDEδ and interfered with KRAS-PDEδ interaction. It influenced the distribution of KRAS in Mia PaCa-2 cells, downregulated the phosphorylation of t-ERK and t-AKT and promoted apoptosis of the cells. The novel inhibitor 36l exhibited significant in vivo antitumor potency in pancreatic cancer patient-derived xenograft (PDX) models. It represents a promising lead compound for investigating the druggability of KRAS‒PDEδ interaction.